Factors That Influence the Performance of Implementing Nurses in The Intensive Care Room of Raden Mattaher Hospital - Novi Septiani; Yuli Prapancha Satar; Sonya Dewi Wulandari (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The performance of nurses in intensive care units is a critical component in ensuring the quality of hospital healthcare services, particularly for critically ill patients requiring intensive care, procedural accuracy, and swift, precise decision-making. Units such as the ICU, ICCU, NICU, PICU, and Stroke Unit at Raden Mattaher General Hospital in Jambi exhibit high workload, complex technical demands, and intense psychological pressure. Therefore, it is important to identify the factors influencing nurses' performance in these intensive care units. This study aims to analyze the relationships among workload, work stress, incentives, tenure, and competence, and the performance of practicing nurses. The study uses a quantitative approach with a cross-sectional design. The sample consists of 115 practicing nurses who meet the inclusion and exclusion criteria. Data were collected using a closed-ended questionnaire. Data analysis was conducted using multivariate tests to examine relationships between independent and dependent variables, and binary logistic regression to determine the contribution of independent variables to nursing performance. The results of this study indicate that workload (p=0.229), work stress (p=0.775), and competence (p=0.065) are not significantly related to nursing performance. However, incentives (p=0.040) and length of service (p=0.017) are significantly related. The logistic regression model indicates that incentives and length of service together account for 11% of the variation in nurse performance (Nagelkerke R² = 0.110). The results of the multivariate analysis indicate that factors emphasizing the provision of proportional incentives and the utilization of length of service in career development can improve nursing performance. In conclusion, improvements in nursing performance can be achieved by strengthening the compensation system, fostering experience-based career development, and empowering human resources sustainably.